Case report: Multidrug resistant gestational trophoblastic neoplasia: focus on failure of immunotherapy and success of high-dose chemotherapy - Enuset, Anne; Duck, Lionel; Petre, Claudia; Machiels, Jean-Pascal; Goffin, Frédéric (Frontiers in Oncology, 2024)
Gestational trophoblastic neoplasia (GTN) is extremely rare, but has a very good prognosis, with a cure rate close to 100%, for low-risk diseases. This article describes the case of a healthy 28-year-old nulliparous patient with GTN resistant to multiple lines of treatment. The era of immunotherapy is revolutionizing oncology, having already proved its worth in the treatment of many cancers. This article will have a specific focus on the emerging role of immunotherapy in the treatment of GTN. Unfortunately, the use of an immune checkpoint inhibitor (ICI) failed in our case, emphasizing on the necessity to clearly define the future role of immune therapy in GTN. Finally, given the rapid progression of the disease after hysterectomy, induction with Paclitaxel- Ifosfamide and then intensification with high-dose Carboplatin and Etoposide with peripheral blood stem cell support was given as a rescue therapy with still curative intent.